Shorter Path Design and Control for an Underactuated Satellite - Jung-Hyung Lee; Donghoon Kim; Jichul Kim; Hwa-Suk Oh (International Journal of Aerospace Engineering)
In the event of a control failure on an axis of a spacecraft, a target attitude can be achieved by several sequential rotations around the remaining control axes. For a spacecraft actuating with wheels, the form of each submaneuver should be a pure single axis rotation since the failed axis should not be perturbed. The rotation path length in sequential submaneuvers, however, increases extremely but is short under normal conditions. In this work, it is shown that the path length is reduced dramatically by finding a proper number of sequential submaneuvers, especially for the target attitude rotation around the failed axis. A numerical optimization is suggested to obtain the shortest path length and the relevant number of maneuvers. Optimal solutions using the sequential rotation approach are confirmed by numerical simulations.